Promotion of HIV clearance by sensitization of HIV reservoirs to cell death - Li, Min; Sun, Baichao; Dong, Jing; Li, Jian-Rong; Minze, Laurie J.; Chen, Min; Cheng, Chao; Wang, Jin (Frontiers in Immunology, 2025)
IntroductionHIV integrates its proviral DNA into the host genome to establish persistent infection. To promote HIV clearance, we have designed an approach for selective elimination of host cells harboring replication-competent HIV (SECH), through inhibition of autophagy and anti-apoptotic molecules during viral reactivation. SECH approach can clear HIV-infected cells in approximately 50% humanized mice. However, the mechanisms for the resistance of reservoirs to depletion in mice with failure in HIV clearance are unclear.MethodsWe have performed single cell transcriptome analyses of HIV-infected T cells that escaped the treatments, in order to identify cellular pathways that could be targeted to facilitate the deletion of refractory HIV reservoirs.ResultsBy single cell RNA sequencing analyses of T cell reservoirs resistant to SECH treatments, we found increases in pro-survival autophagy and glycolysis. Moreover, these resistant reservoirs expressed more epigenetic modifiers that repress HIV gene expression, while targeting such epigenetic repression promoted cell death in HIV-infected cells.DiscussionOur results indicate that T cell reservoirs refractory to depletion maintain a delicate balance between low levels of HIV gene expression and evasion of cell death. This study suggests that targeting epigenetic repression of HIV is critical for the depletion of the viral reservoirs.